Transparency in Action: A Study on Whistleblowing Intention within Malaysia’s Banking Sector - Munap, Rudzi Binti; Obeto, Mercy Nwadiuto; Zainal, Noor Azra Saliha Binti; Rahim, Nurnisya Adriana Binti; Amin, Mohd Adzmin Shahfeezan Bin Mohd (International Review of Management and Marketing, 2025)
Effective whistleblowing systems are crucial for organizations to detect and address misconduct. Encouraging employees to report misconduct is challenging due to multiple individual and contextual influences. This study examines the relationship between attitude, subjective norms, and perceived behavioral control on whistleblowing intentions, while considering the mediating role of psychological safety. Employing a purposive sampling approach, the sample consisted of 138 non-managerial employees from five banks located in Perlis, Malaysia. Data was collected through the distribution of questionnaires via Google Forms and analyzed using descriptive and inferential statistical techniques in SPSS and AMOS software version 29. The measurement model confirms that model fits the date, the structural model indicated that the relationship between attitude, perceived behavioral control and whistleblowing intentions was not significant. However, there was a positive relationship between subjective norms, psychological safety, and whistleblowing intentions. The study illustrated that psychological safety does not mediate the relationship between attitude, subjective norms, perceived behavioral control and whistleblowing intentions. This study contributes to the understudied context of whistleblowing in the Malaysian banking sector, elucidating the interplay between individual and contextual factors shaping whistleblowing decisions, with implications for organizations seeking to cultivate ethical environments and effective whistleblowing channels.